2017
DOI: 10.3892/mmr.2017.7295
|View full text |Cite
|
Sign up to set email alerts
|

Betaine attenuates chronic alcohol-induced fatty liver by broadly regulating hepatic lipid metabolism

Abstract: Betaine has previously been demonstrated to protect the liver against alcohol-induced fat accumulation. However, the mechanism through which betaine affects alcohol-induced hepatic lipid metabolic disorders has not been extensively studied. The present study aimed to investigate the effect of betaine on alcoholic simple fatty liver and hepatic lipid metabolism disorders. A total of 36 rats were randomly divided into control, ethanol and ethanol + betaine groups. Liver function, morphological alterations, lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 38 publications
(41 reference statements)
2
40
0
Order By: Relevance
“…Previous study reported betaine administration can attenuate chronic alcohol-induced hepatic cholesterol accumulation ( Yang et al., 2017 ), which was associated with downregulated mRNA expression of SREBP2 and HMGCR. Consistent with these results, hepatic SREBP2 and HMGCR mRNA and protein expression were markedly reduced in the betaine group compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study reported betaine administration can attenuate chronic alcohol-induced hepatic cholesterol accumulation ( Yang et al., 2017 ), which was associated with downregulated mRNA expression of SREBP2 and HMGCR. Consistent with these results, hepatic SREBP2 and HMGCR mRNA and protein expression were markedly reduced in the betaine group compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Betaine is the trimethyl derivative of glycine that can be obtained directly from diet or indirectly from dietary choline via oxidation ( Lever and Slow, 2010 ). Betaine can activate DNA methylation through one carbon metabolism and thus regulates the transcription of cholesterol metabolic genes ( Yang et al., 2017 , Hu et al., 2018 ). Recent study provided the evidence that maternal betaine exposure enhances hepatic cholesterol accumulation along with hypermethylation of CYP7A1 gene promoter ( Zhao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol has been postulated to have multiple effects on hepatic lipid metabolism including increased fatty acid uptake and de novo lipogenesis, as well as decreased fatty acid oxidation and very low density lipoprotein (VLDL) secretion, although the relative contribution of these different factors is unknown (Baraona and Lieber, ; Orman et al., ). Regarding TG synthesis, chronic alcohol consumption increases the hepatic expression of genes involved in TG synthesis, suggesting a direct role of this pathway in the development of alcoholic steatosis (Clugston et al., , ; Wang et al., ; Yang et al., ).…”
mentioning
confidence: 99%
“…While there has been considerable focus on the role of DGAT1 and DGAT2 in the context of NAFLD, there have been no mechanistic studies exploring their role in ALD, with the extant literature primarily focused on the effect of alcohol on the expression level of these enzymes. For example, expression of Dgat1 and Dgat2 has both been reported to be increased in response to alcohol feeding in mice, rats, and the human HepG2 cells (Clugston et al., , ; Wang et al., ; Yang et al., ). Wang and colleagues (2010) further suggested a direct role of DGAT2 in the pathogenesis of ALD by contributing to hepatic steatosis in association with increased de novo lipogenesis.…”
mentioning
confidence: 99%
“…Although several studies of betaine have been performed in pre-clinical (animal) studies, only SAM has been evaluated in patients with alcoholic liver disease[ 10 , 11 ]. In the first randomized, double-blind, placebo-controlled study, SAM improved survival and/or delayed listing for liver transplantation in 123 patients with alcoholic cirrhosis[ 12 ].…”
Section: Introductionmentioning
confidence: 99%